Standing with Standing Rock : voices from the #NoDAPL movement - Estes, Nick; Dhillon, Jaskiran, 1974- (Indigenous Americas., 2019)
"Amid the Standing Rock movement to protect the land and the water that millions depend on for life, the Oceti Sakowin (the Dakota, Nakota, and Lakota people) reunited. Through poetry and prose, essays, photography, interviews, and polemical interventions, the contributors reflect on Indigenous history and politics and on the movement's significance. Their work challenges our understanding of colonial history not simply as "lessons learned" but as essential guideposts for activism"--